Prognostic importance of NT-proBNP following high-risk myocardial infarction in the PARADISE-MI Trial. (3rd October 2022) - Jering, K; Claggett, B; Pfeffer, M A; Granger, C; Kober, L; Lewis, E F; Maggioni, A P; Mann, D L; McMurray, J J V; Prescott, M F; Rouleau, J L; Solomon, S D; et al.
Abstract: Background/Introduction: N-terminal pro-B-type natriuretic peptide (NT-proBNP) is a marker of ventricular wall stress and a potent predictor of death and heart failure (HF) across multiple populations (from healthy insurance applicants to various disease entities). Purpose: To evaluate the prognostic importance of NT-proBNP in patients with acute myocardial infarction (AMI) complicated by left ventricular systolic dysfunction, pulmonary congestion, or both and ≥1 of 8 predefined risk-augmenting factors (age ≥70 years, diabetes, previous MI, eGFR <60 ml/min/1.73 m 2, atrial fibrillation, LVEF <30%, Killip class III/IV, or ST elevation MI without reperfusion) enrolled in PARADISE-MI. Methods: Patients were randomized to sacubitril/valsartan 200mg or ramipril 5mg twice daily within 0.5 to 7 days of presenting with an AMI. Patients with prior HF were excluded. NT-proBNP and high-sensitivity troponin T (hsTnT) were collected at randomization in a prespecified sub-study of 1129 patients. The primary endpoint of PARADISE-MI was a time-to-first composite of cardiovascular (CV) death or incident HF (hospitalization or outpatient symptomatic HF); secondary endpoints included all-cause death and the composite of fatal or non-fatal MI or stroke. Results: Median NT-proBNP was 1757 pg/ml [interquartile range, 896–3462 pg/ml] at randomization (4.0±1.8 days after presentation with the index MI). Patients with higher NT-proBNP levels at baseline were older, more commonly women and more frequently had hypertension, atrial fibrillation, renal dysfunction, and pulmonary congestion at randomization (all p<0.001). NT-proBNP concentrations were only weakly correlated with levels of hsTnT at randomization (r=0.38, p<0.001). NT-proBNP at baseline was strongly associated with the primary composite endpoint (adjusted HR 1.45 per doubling NT-proBNP; 95% CI, 1.23–1.70), independent of clinical variables as well as hsTnT (Figure). NT-proBNP was also independently associated with all-cause death (aHR 1.74; 95% CI, 1.38–2.21) and fatal or non-fatal MI or stroke (aHR 1.24; 95% CI, 1.05–1.45). The relative effect of sacubitril/valsartan versus ramipril on the primary composite endpoint was not statistically different across the spectrum of NT-proBNP (p-interaction = 0.46). Conclusions: When assessed within the first week of a high risk AMI NT-proBNP is not only associated with incident HF and death but also with atherosclerotic events and provides prognostic information that is independent of hsTnT in this post AMI population. Funding Acknowledgement: Type of funding sources: None.